Guiding principles for undergraduate medical education in the time of the COVID-19 pandemic. (1st February 2021) - Muller, David; Parkas, Valerie; Amiel, Jonathan; Anand, Shashi; Cassese, Todd; Cunningham, Tara; Kang, Yoon; Nosanchuk, Joshua; Soriano, Rainier; Zbar, Lori; Karani, Reena
Abstract: As the early epicenter of the COVID-19 pandemic, New York City's medical schools experienced dramatic disruptions in every aspect of medical education. Remote learning was created, seemingly overnight, clerkships were disrupted, licensing examinations were cancelled, teaching faculty were redeployed, student volunteers rallied, and everyone was required to shelter at home. Seismic changes were required to adapt the authors' educational programs to a constantly evolving, unpredictable, and ever-worsening public health crisis. Entirely new communication strategies were adopted and thousands of decisions had to be made, often with little time to carefully reflect on the consequences of those decisions. What allowed each school to navigate these treacherous waters was a set of guiding principles that were used to ground each conversation, and inform every decision. While the language varied somewhat between schools, the core principles were universal and framed a way forward at a time when information, data, precedent, and best practices did not exist. The authors share these guiding principles in the hope that colleagues at other medical schools will find them to be a useful framework as we all continue to cope with the impact of COVID-19 on the future of medical education.